2019
DOI: 10.3390/ijms20225566
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Fatty Acid- and Retinoid-Binding Protein Gene (Ar-far-1) from the Chrysanthemum Foliar Nematode, Aphelenchoides ritzemabosi

Abstract: The chrysanthemum foliar nematode (CFN), Aphelenchoides ritzemabosi, is a migratory, plant-parasitic nematode that is widely distributed and infects the aboveground parts of many plants. The fatty acid- and retinoid-binding proteins (FAR) are nematode-specific proteins that are involved in the development, reproduction, and infection of nematodes and are secreted into the tissues to disrupt the plant defense reaction. In this study, we obtained the full-length sequence of the FAR gene (Ar-far-1) from CFN, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…However, either free fatty acids or free retinoids are relatively insoluble in water, susceptible to oxidation, and potentially toxic to nematodes [ 19 , 44 ]. FARs represent one of the approaches evolved by nematodes to acquire and transport free fatty acids and retinol [ 19 , 26 , 44 , 57 , 58 ]. Therefore, FAR protein-coding genes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, either free fatty acids or free retinoids are relatively insoluble in water, susceptible to oxidation, and potentially toxic to nematodes [ 19 , 44 ]. FARs represent one of the approaches evolved by nematodes to acquire and transport free fatty acids and retinol [ 19 , 26 , 44 , 57 , 58 ]. Therefore, FAR protein-coding genes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary progress has been made in the study of the sequence characteristics, basic functional properties, and binding activity with FAR proteins [ 9 , 13 , 27 ]. However, to date, there are still no reports on their specific functions in nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids and retinols play important roles in physiological processes, such as gene activation, cell signaling pathways, tissue differentiation, and repair, and may inhibit or interfere with the host’s defensive immune response [ 8 , 9 ]. As a unique protein in nematodes, more than 70 FAR sequences and functions have been identified in different species of nematodes [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The function of the FAR protein gene ( far ) in five species of plant nematodes has been studied and verified by RNA interference (RNAi) [ 8 , 12 , 15 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid and retinol-binding proteins (FAR) are among the most widely studied proteins secreted by the body wall of nematodes, and have been widely reported in free-living nematodes, animal-parasitic nematodes, and plant-parasitic nematodes [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. At present, the structures and functions of FAR are mainly explained as follows: (1) FAR are unique to nematodes and do not exist in other biological groups [ 38 ]; (2) their function in obtaining fatty acids and retinols from hosts and the environment is necessary for nematode lipid biosynthesis and assembly of macromolecular structures to complete the growth and development of nematodes [ 31 , 32 ]; (3) most of them are located on the nematode body wall, which is the host–parasite interface, and, therefore, they play important roles in promoting nematode parasitism and regulating host defences [ 30 ]; and (4) there is evidence that FAR can influence the fecundity and pathogenicity of nematodes [ 32 , 33 , 39 ]. In previous studies, we found eight FAR proteins with significantly different mRNA localisations and diverse functions in RWTNs [ 32 , 33 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the structures and functions of FAR are mainly explained as follows: (1) FAR are unique to nematodes and do not exist in other biological groups [ 38 ]; (2) their function in obtaining fatty acids and retinols from hosts and the environment is necessary for nematode lipid biosynthesis and assembly of macromolecular structures to complete the growth and development of nematodes [ 31 , 32 ]; (3) most of them are located on the nematode body wall, which is the host–parasite interface, and, therefore, they play important roles in promoting nematode parasitism and regulating host defences [ 30 ]; and (4) there is evidence that FAR can influence the fecundity and pathogenicity of nematodes [ 32 , 33 , 39 ]. In previous studies, we found eight FAR proteins with significantly different mRNA localisations and diverse functions in RWTNs [ 32 , 33 , 39 ]. The expression level of Ab-far-1 was significantly higher than that of other FAR genes in RWTNs.…”
Section: Introductionmentioning
confidence: 99%